INVESTIGATION OF STOICHIOMETRIC «AIR-FUEL» RATIO OF ORGANIC COMPOUNDS. PART 2. ALKENES, ALKYNES - Запорожець, А. О. (Science-based technologies, 2014)
The article considered features of formation the stoichiometric “air-fuel” ratio of organic hydrocarbons, such as alkenes and alkynes. The main objective of this work is to establish the regularities of the formation of the stoichiometric “air-fuel” ratio for the first 10 members of the alkene’s (ethylene, propene, butane, pentene, hexene, heptene, octene, nonene, decene, undecene) and alkynes (acetylene, propyne, butyne, pentyne, hexyne, heptyne, octyne, nonyne, decyne, undecyne) homologous series. Analyzed the chemical and physical properties of alkenes and alkynes, which influence on the formation of the optimal fuel mixtures. Showing the dependences of the changing of the air mass which consumed from the excess air ratio during combustion of perfectly clean fuel materials. The energy analyze of the unsaturated hydrocarbons combustion’s are performed. Showing the exact mass values of the “air-fuel” ratio for the formation of stoichiometric mixtures of alkenes and alkynes. Set the fact of reducing of the optimal air mass for the formation of flammable mixtures alkynes and stability of “air-fuel” ratio of alkenes under increasing of the homologous difference of alkanes. The results of investigation can be used for regulation the combustion regimes in the internal combustion engines of a car, furnaces boilers and household appliance worked on gaseous and liquid hydrocarbons (alkanes).